Invasive enteritis by Strongyloides stercoralis presenting as acute abdominal distress under corticosteroid therapy. - Rodrigues, M. A.; Fróes, R. C.; Anefalos, A.; Kobayasi, S. (FapUNIFESP (SciELO), 2001)
Overwhelming helminthiasis is still a problem in endemic areas, especially in immunocompromised patients. We report a case of invasive intestinal strongyloidiasis that was clinically expressed as acute abdominal distress in a 73-year-old man from São Paulo who had been receiving methylprednisone, 20 mg/day, for one year for osteoarthritis. A surgical specimen from the ileum revealed invasive enteritis with severe infestation by Strongyloides stercoralis. The patient died of sepsis 6 days after surgery. The possibility of invasive strongyloidiasis should be considered in the differential diagnosis of acute abdominal distress in patients undergoing immunosuppressive therapy.
Keywords: glucocorticoid; methylprednisolone; acute abdomen; aged; case report; enteritis; fatality; human; male; osteoarthritis; parasitology; pathology; strongyloidiasis; Abdomen, Acute; Aged; Enteritis; Fatal Outcome; Glucocorticoids; Humans; Male; Methylprednisolone; Osteoarthritis; Strongyloidiasis